2022
DOI: 10.3390/v14040674
|View full text |Cite
|
Sign up to set email alerts
|

VZV Infection of Primary Human Adrenal Cortical Cells Produces a Proinflammatory Environment without Cell Death

Abstract: Virus infection of adrenal glands can disrupt secretion of mineralocorticoids, glucocorticoids, and sex hormones from the cortex and catecholamines from the medulla, leading to a constellation of symptoms such as fatigue, dizziness, weight loss, nausea, and muscle and joint pain. Specifically, varicella zoster virus (VZV) can produce bilateral adrenal hemorrhage and adrenal insufficiency during primary infection or following reactivation. However, the mechanisms by which VZV affects the adrenal glands are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Few studies have reported infections of the adrenal glands thus far [126,149]. Hence, this is a novel report that describes all aspects of adrenal abscesses based on the currently available literature.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Few studies have reported infections of the adrenal glands thus far [126,149]. Hence, this is a novel report that describes all aspects of adrenal abscesses based on the currently available literature.…”
Section: Discussionmentioning
confidence: 94%
“…It is likely that not all cases of adrenal abscesses have been reported and the ones with unusual pathogens or unexpected outcomes are more likely to be reported. Finally, we have not described viral adrenalitis in this review, since our focus was on the abscesses and since it has been described already elsewhere [149].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Evidence of the presence of several other viruses in the endocrine organs is available for human T-cell lymphotropic virus-1, herpes simplex virus, rubella, mumps virus, Epstein–Barr virus, varicella zoster virus, cytomegalovirus, human foamy virus, and Simian virus 40, and these viruses have been associated with various endocrine diseases [ 173 , 174 , 175 , 176 ]. Viruses can transiently or permanently influence the functions of endocrine organs through direct damage of endocrine cells or through indirect mechanisms, especially through the activation of the host antiviral immune response, which may lead to the development of local or systemic inflammation or organ-specific autoimmunity that results in certain endocrinopathies.…”
Section: Discussionmentioning
confidence: 99%